Marine heatwaves alter shell microbiomes and denitrification capacity: An oyster family-specific response - Giulia Filippini; Ana B. Bugnot; Wayne O'Connor; Paul E. Gribben; Deepa R. Varkey; Ian T. Paulsen; Katherine A. Dafforn (Marine Pollution Bulletin, 2026)

Oral delivery of an ustekinumab biosimilar with bioavailability comparable to subcutaneous administration in healthy human participants - Joshua T. Myers; Alyson Yamaguchi; Kyle Horlen; Leonard C. Fung; April Toledo Vo; Deepa Mohan; Mary Hoopes; Mir Imran; Jacques Van Dam; Ofer M. Gonen; Mir A. Hashim; Arvinder K. Dhalla; et al. (European Journal of Clinical Pharmacology, 2026)

LP-53 Evaluation of the Mutagenic Potential of 1-Cyclopentyl-4-Nitrosopiperazine Nitrosamine in Human Lymphoblastoid TK6and CHO-K1 Cells - M. Shameer P; T. Pradeep; M. Rajini; A. Mariappan; S. Sandhya; G. Kulavardhan; M. Sumithra; R. Harika; A. Varun; K. Mohan; V. Deepa (Toxicology Letters, 2025)

Exploring climate-driven phenological mismatches in pears, pests and natural enemies: a multi-model approach - Laura A. Reeves; Tim Belien; Deepa Senapathi; Michael P. D. Garratt; Michelle T. Fountain (Journal of Pest Science, 2025)
Pear psyllid ( Cacopsylla pyri ) is the dominant pest of UK pear orchards, with an estimated cost of £5 million per annum. Insecticide withdrawal and increased pesticide resistance of C. pyri have led many growers to depend more on natural enemies for pest management, including earwigs. However, there is concern how phenological events may shift with future climate change, which may result in phenological mismatches. This study aimed to determine shifts in timing of phenological events within an agroecosystem and predict phenological mismatches or synchronies between trophic levels. We evaluated three models: the C. pyri phenology model, the earwig degree day model and the PhenoFlex model (flowering time). Phenological events predicted by models included: first, full and last flowering time for Pyrus communis ; peak psyllid abundance date for first-generation (G1) C. pyri nymphs and second-generation (G2) eggs, nymphs and adults; and peak abundance date for stage 4 Forficula auricularia and adults. Findings indicated that the timing of phenological events was advancing for all trophic levels, becoming significantly earlier under the current time period. Furthermore, predictions indicated that timing events would continue to advance under the RCP8.5 scenario. However, not all phenological events advanced at the same rate; the date of peak C. pyri G1 nymph abundance advanced at a higher rate than full flowering time, which could result in a phenological mismatch by 2071. Conversely, C. pyri and F. auricularia showed phenological synchrony, with peak abundance dates advancing at a similar rate, which could be beneficial for future biological control.

Intraguild Predation or Spatial Separation? The efficacy and Interactions of Two Natural Enemy Species for the Biological Control of Pear Psyllid (Cacopsylla pyri) - Laura A. Reeves; Michelle T. Fountain; Michael P. D. Garratt; Deepa Senapathi (Journal of Insect Behavior, 2024)
Pear psyllid ( Cacopsylla pyri ) is a persistent pest to the pear industry; with an estimated cost of £5 million per annum in the UK alone. This phloem feeding insect is resistant to a large proportion of approved pesticides, necessitating the use of alternative control strategies. Many pear growers practice integrated pest management (IPM) of pear psyllid, focusing on maximizing natural enemy populations, whilst minimizing the use of agrochemical sprays. The anthocorid Anthocoris nemoralis and the European earwig Forficula auricularia are particularly effective at controlling pear psyllid populations during the summer months. Despite the effectiveness of both natural enemies, there is a lack of understanding on whether both species should be promoted together or separately, due to the risk of intraguild predation (IGP) or interference competition. Furthermore, abiotic factors including temperature may influence both behaviors, altering activity level and niche overlap. Although IGP and interference competition have been documented between multiple species of natural enemies neither have been studied between these two specific predators. Using microcosm experiments, olfactometer assays and survival analyses this study demonstrated whether A. nemoralis and F. auricularia can be used in synchrony to control pear psyllid. Results indicated that IGP is present; F. auricularia will consume A. nemoralis when predators are not spatially separate and in absence of psyllid prey. There was no evidence for interference competition, although both predators consumed more prey at higher temperatures. This confirms that pear growers can encourage both predators for the control of pear psyllid without losing predation efficacy.

A whole ecosystem approach to pear psyllid (Cacopsylla pyri) management in a changing climate - Laura A. Reeves; Michael P. D. Garratt; Michelle T. Fountain; Deepa Senapathi (Journal of Pest Science, 2024)
Whole ecosystem-based approaches are becoming increasingly common in pest management within agricultural systems. These strategies consider all trophic levels and abiotic processes within an ecosystem, including interactions between different factors. This review outlines a whole ecosystem approach to the integrated pest management of pear psyllid ( Cacopsylla pyri Linnaeus) within pear ( Pyrus communis L.) orchards, focusing on potential disruptions as a result of climate change. Pear psyllid is estimated to cost the UK pear industry £5 million per annum and has a significant economic impact on pear production globally. Pesticide resistance is well documented in psyllids, leading to many growers to rely on biological control using natural enemies during the summer months. In addition, multiple insecticides commonly used in pear psyllid control have been withdrawn from the UK and Europe, emphasising the need for alternative control methods. There is growing concern that climate change could alter trophic interactions and phenological events within agroecosystems. For example, warmer temperatures could lead to earlier pear flowering and pest emergence, as well as faster insect development rates and altered activity levels. If climate change impacts pear psyllid differently to natural enemies, then trophic mismatches could occur, impacting pest populations. This review aims to evaluate current strategies used in C. pyri management, discuss trophic interactions within this agroecosystem and highlight potential changes in the top-down and bottom-up control of C. pyri as a result of climate change. This review provides a recommended approach to pear psyllid management, identifies evidence gaps and outlines areas of future research.

Chemosensitizing potential of andrographolide in P-glycoprotein overexpressing multidrug-resistant cancer cell lines - Deepa Swati Lakra; Pradhapsingh B; Deepika N; Dhanalakshmi T; Kanimozhi G; Rajendra Prasad N (Natural Product Research, 2024)

Functional and Behavioral Responses of the Natural Enemy Anthocoris nemoralis to Cacopsylla pyri, at Different Temperatures - Laura A. Reeves; Michael P. D. Garratt; Michelle T. Fountain; Deepa Senapathi (Journal of Insect Behavior, 2023)
Anthocoris nemoralis is the dominant predator of pear sucker ( Cacopsylla pyri ) in the UK. Anthocoris nemoralis migrates into orchards in spring or is introduced as a biocontrol agent, reaching peak population levels in July-August, contributing to effective control of summer pear sucker populations. However, due to temperature dependent development and metabolism there are concerns that C. pyri populations or feeding rates may increase due to changing climatic conditions. Thus, how A. nemoralis responds to temperature, impacts its ability as a biocontrol agent. Functional response assays, monitoring attack rate and handling time of A. nemoralis and behavioral assays, using Ethovision tracking software occurred, to assess the impact of temperature on predation. Experiments were conducted at current and future July-August mean temperatures, predicted using RCP4.5 and RCP8.5 (medium and high, representative concentration pathway) emissions scenarios, using 2018 UK Climate Projections (UKCP18). All treatments demonstrated a Type II functional response, with female anthocorids demonstrating shorter handling times and higher attack rates than males. Males showed longer prey handling times at 18 °C compared to 23 °C and more time was spent active at lower temperatures for both sexes. Females did not show significant differences in attack rate or handling time in response to temperature. Overall prey consumption was also not significantly affected by temperature for either sex. This study suggests that anthocorids are likely to remain effective natural enemies under future predicted temperatures, due to non-significant differences in prey consumption.

Assessment of Spatial and Temporal Changes in Water Quality of a Tropical River in Southern Western Ghats, Kerala, India, Using Physicochemical Quality Indices and Multivariate Analysis - Ajoy Saha; T. T. Paul; Deepa Sudheesan; Sravan Kumar Sharma; V. R. Suresh; B. K. Das; S. Manoharan; M. E. Vijaykumar; S. Samanta; Chayna Jana (Natural Resources Research, 2022)

High-frequency direct shoot induction from leaf explants of Pogostemon quadrifolius (Benth.) F. Muell.: an ethnomedicinal herb - A. V. Deepa; T. Dennis Thomas (In Vitro Cellular & Developmental Biology - Plant, 2022)

Evidence for Semiochemical Divergence Between Sibling Bark Beetle Species: Dendroctonus brevicomis and Dendroctonus barberi - Brian T. Sullivan; Amanda M. Grady; Richard W. Hofstetter; Deepa S. Pureswaran; Cavell Brownie; Daniel Cluck; Tom W. Coleman; Andrew Graves; Elizabeth Willhite; Lia Spiegel; Dwight Scarbrough; Andrew Orlemann; et al. (Journal of Chemical Ecology, 2021)

Optimization and scale-up of laccase production by Bacillus sp. BAB-4151 isolated from the waste of the soap industry - T. Deepa; A. K. Gangwane; R. Z. Sayyed; H. P. Jadhav; Mehjabeen (Environmental Sustainability, 2020)

In vitro strategies for the conservation of Indian medicinal climbers - A. V. Deepa; T. Dennis Thomas (In Vitro Cellular & Developmental Biology - Plant, 2020)

Chickpea wilt: status, diagnostics and management - Gururaj Sunkad; H. Deepa; T. H. Shruthi; Dinesh Singh (Indian Phytopathology, 2019)

Sp1 Binding Site Polymorphism at COL1A1 Gene and Its Relation to Bone Mineral Density for Osteoporosis Risk Factor Among the Sikkimese Men and Women of Northeast India - Deepa Soibam; T. A. Singh; Parvati Nandy; Sunder Kishore Dewan; Ankur Baruah (Indian Journal of Clinical Biochemistry, 2019)

Synthesis of magnetic carbon nanocomposites by hydrothermal carbonization and pyrolysis - M. T. H. Siddiqui; Sabzoi Nizamuddin; Humair Ahmed Baloch; N. M. Mubarak; Deepa K. Dumbre; Inamuddin; Abdullah M. Asiri; A. W. Bhutto; Madapusi Srinivasan; G. J. Griffin (Environmental Chemistry Letters, 2018)

Erratum to: Western Pine Beetle Populations in Arizona and California Differ in the Composition of Their Aggregation Pheromones - Deepa S. Pureswaran; Richard W. Hofstetter; Brian T. Sullivan; Amanda M. Grady; Cavell Brownie (Journal of Chemical Ecology, 2016)

Western Pine Beetle Populations in Arizona and California Differ in the Composition of Their Aggregation Pheromones - Deepa S. Pureswaran; Richard W. Hofstetter; Brian T. Sullivan; Amanda M. Grady; Cavell Brownie (Journal of Chemical Ecology, 2016)

Comparative Transcriptome Analysis of Two Species of Curcuma Contrasting in a High-Value Compound Curcumin: Insights into Genetic Basis and Regulation of Biosynthesis - T. E. Sheeja; K. Deepa; R. Santhi; B. Sasikumar (Plant Molecular Biology Reporter, 2015)

Acute Toxicity Assessment of Reactive Red 120 to Certain Aquatic Organisms - R. Darsana; G. Chandrasehar; V. Deepa; Y. Gowthami; T. Chitrikha; S. Ayyappan; A. Goparaju (Bulletin of Environmental Contamination and Toxicology, 2015)

The effect of flavanol-rich cocoa on cerebral perfusion in healthy older adults during conscious resting state: a placebo controlled, crossover, acute trial - Daniel J. Lamport; Deepa Pal; Christina Moutsiana; David T. Field; Claire M. Williams; Jeremy P. E. Spencer; Laurie T. Butler (Psychopharmacology, 2015)

Following Natures Lead: On the Construction of Membrane-Inserted Toxins in Lipid Bilayer Nanodiscs - Narahari Akkaladevi; Srayanta Mukherjee; Hiroo Katayama; Blythe Janowiak; Deepa Patel; Edward P. Gogol; Bradley L. Pentelute; R. John Collier; Mark T. Fisher (The Journal of Membrane Biology, 2015)

A simple and efficient protocol for isolation of high quality functional RNA from different tissues of turmeric (Curcuma longa L.) - K. Deepa; T. E. Sheeja; R. Santhi; B. Sasikumar; Anu Cyriac; P. V. Deepesh; D. Prasath (Physiology and Molecular Biology of Plants, 2014)

Loss of P2Y2 Nucleotide Receptors Enhances Early Pathology in the TgCRND8 Mouse Model of Alzheimer's Disease - Deepa Ajit; Lucas T. Woods; Jean M. Camden; Christina N. Thebeau; Farid G. El-Sayed; Glen W. Greeson; Laurie Erb; Michael J. Petris; Douglas C. Miller; Grace Y. Sun; Gary A. Weisman (Molecular Neurobiology, 2014)

Neuroprotective roles of the P2Y2 receptor - Gary A. Weisman; Deepa Ajit; Richard Garrad; Troy S. Peterson; Lucas T. Woods; Christina Thebeau; Jean M. Camden; Laurie Erb (Purinergic Signalling, 2012)

P2 Receptors for Extracellular Nucleotides in the Central Nervous System: Role of P2X7 and P2Y2 Receptor Interactions in Neuroinflammation - Gary A. Weisman; Jean M. Camden; Troy S. Peterson; Deepa Ajit; Lucas T. Woods; Laurie Erb (Molecular Neurobiology, 2012)

High individual variation in pheromone production by tree-killing bark beetles (Coleoptera: Curculionidae: Scolytinae) - Deepa S. Pureswaran; Brian T. Sullivan; Matthew P. Ayres (The Science of Nature, 2007)

Evidence that (+)-endo-Brevicomin is a Male-Produced Component of the Southern Pine Beetle Aggregation Pheromone - Brian T. Sullivan; William P. Shepherd; Deepa S. Pureswaran; Takuya Tashiro; Kenji Mori (Journal of Chemical Ecology, 2007)

Fitness consequences of pheromone production and host selection strategies in a tree-killing bark beetle (Coleoptera: Curculionidae: Scolytinae) - Deepa S. Pureswaran; Brian T. Sullivan; Matthew P. Ayres (Oecologia, 2006)

Role of catalytic function in the antiplatelet activity of phospholipase A2 cobra (Naja naja naja) venom - L.M.S Rudrammaji; K. Deepa Machiah; T.P. Krishna Kantha; T. Veerabasappa Gowda (Molecular and Cellular Biochemistry, 2001)